Designing a Clinic Model for a Restorative Community Justice Partnership - Susan L. Brooks; Rachel E. Lopez (Washington University Journal of Law & Policy, 2015)
In a previous Article, co-author Susan Brooks and her colleagues challenged the traditional understanding of what it meant to be a community lawyer and instead defined the engagement as “an approach to the practice of law and to clinical legal education that centers on building and sustaining relationships with clients, over time, in context, as a part of and in conjunction with communities.” This Article highlights the efforts of Brooks and Lopez to create a Community Lawyering Clinic (CLC) at Drexel University’s Thomas R. Kline School of Law. In particular, the duo reflect on two questions kept in mind during the development of the CLC: how to ensure that the work of the clinic reflects and incorporates the diverse desires and demands of the community, and how to facilitate an environment that encourages a community partnership characterized by equality.
Keywords: community lawyering; clinical education